Evaluation of droplet and aerosol dispersion: a biosafety alert for the dental surgeon in the context of the COVID-19 pandemic (Research, Society and Development, 2022)
The pandemic of COVID-19 has called into question the risks of infection in dentistry. This research is justified by the need to demonstrate the occupational risks that droplets and aerosols pose to the dental surgeon. The study aims to analyze the dispersion of aerosol droplets in a dental environment and the effectiveness of PPE. We used simulations of a procedure in a dental office covered with white TNT, with the water in the reservoir stained with food coloring, and two models playing the role of the attendant and the patient. To keep the simulation closer to reality, two devices made of acrylic resin were superimposed on the patient's arch. The steps were photographed for data recording, analysis, and future comparisons. After the simulation, spills were found on the TNT that covered the floor, on the office table, and on the spittoon. The personal protective equipment used by the attendant was where the highest concentration of splashes was observed, especially on the disposable apron and the face shield. The ability to disperse droplets and aerosols was evidenced in this study. Droplets and aerosols represent a health risk for the dental surgeon. Biosafety care should be part of the daily routine of professionals.